Asymptotically J_σ-Equivalence of Sequences of Sets - Uğur Ulusu; Esra Gülle (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
In thisstudy, we introduce the concepts of Wijsman asymptotically J-invariant equivalence (WLJσ) ,Wijsman asymptotically strongly p-invariant equivalence([WLVσ)]p) and Wijsman asymptotically J*-invariant equivalence(WLJ*σ). Also, we investigate the relationships among the conceptsof Wijsman asymptotically invariant equivalence, Wijsman asymptoticallyinvariant statistical equivalence,WLJσ,[WLVσ)]pandWLJ*σ.